The Impact of Halal Label Availability on Fried Chicken Purchase Decisions: A Case Study in Jatirogo District, Tuban Regency - Kristiyoningsih; Awaludin Ridwan; Ahmad Fanani (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2023)
Fried chicken is a dish made by coating chicken in flour and then deep-frying it, resulting in a crispy outer layer and tender meat inside. It has become a popular processed food choice that is readily available and offers various prices, making it a promising franchise business.  With the government's strict regulations on food safety, including halal food requirements, many fried chicken entrepreneurs display halal certificates in their outlets to attract customers.  This study aimed to investigate whether the availability of halal labels influences the purchase decision of fried chicken among consumers.  Data was collected using questionnaires. The respondents were collected using Non-Probability Sampling.  Then they were analyzed through the Simple Regression Test in SPSS.  The results showed that 61.9% of consumers considered halal variables as a factor in their purchasing decision, suggesting that halal labels influence consumers' buying behavior.  This finding is in line with the fact that the majority of the people in Jatirogo Subdistrict are Muslim, and halal food is a significant requirement for them.  The study highlights the importance of understanding the characteristics and needs of consumers in the culinary business and the significance of halal certification in attracting Muslim consumers.  This research serves as a valuable evaluation material for culinary business developers to better understand their target market and cater to their needs to attract more customers.